Susceptibility to Malathion of Aedes aegypti Mosquito Population from Tangkerang Barat, Marpoyan Damai Distric (Future Science, 2022)
The use of chemical insecticides to control Aedes aegypti (Ae. aegypti) mosquitoes, as the main vector of dengue hemorrhagic fever (DHF), has long been used. Malathion is an organophosphate insecticide that is commonly used to control mosquitoes. Monitoring of insecticide resistance is an important part of entomological surveillance. This study aimed to determine the susceptibility status of Ae. aegypti to 5% malathion in Tangkerang Barat Sub District, Marpoyan Damai District. This study was conducted in August - October 2022. This study was a descriptive study with a cross-sectional design. Samples of adult mosquitoes (F1) that came from larvae were collected from 100 houses in Tangkerang Barat according by Health Ministry for susceptibility tests and reared at the Parasitology Laboratory of the Faculty of Medicine until adult mosqitoes. The experiment was carried out using 5% malathion-impregnated paper according to the protocol of the WHO bioassay test. Twenty-five of adult mosquitoes were exposed to 5% malathion-impregnated paper in each of 4 exposure tubes and 2 control tubes for 1 hour then moved to hold tube and maintained for 24 hours The mortality of Ae. aegypti after 24 hours were 100%. The susceptibility status of Ae. aegypti mosquitoes to 5% malathion in Tangkerang Barat was susceptible. Malathion can be used against adult Ae.aegypti mosquitoes in Tangkerang Barat but still need to rotate the insecticide. The use of efficacious and safe insecticides against Ae.aegypti is one of the most effective ways to interrupt the transmission of DHF. Rotating the insecticide class is important to continue vector control.